GAMBARAN PERILAKU HIDUP BERSIH DAN SEHAT SANTRIWATI PONDOK PESANTREN PERSIS 80 AL AMIN SINDANGKASIH CIAMIS - Iis Wahyuni Choerunnisa; Nova Dahliana (Jurnal Kesehatan Bakti Tunas Husada: Jurnal Ilmu-ilmu Keperawatan, Analis Kesehatan dan Farmasi, 2023)
Clean and Healthy Living Behavior (PHBS) in Islamic Boarding Schools is a set of behaviors that are practiced on the basis of awareness as learning outcomes, which make the Islamic boarding school community independently able to prevent disease, improve their health, and play an active role in creating a healthy environment. Islamic Association Islamic Boarding School 80 Al Amin is one of the Islamic boarding schools in the Ciamis Regency area that has implemented PHBS in the pesantren environment. Research is a qualitative field research that intends to understand the phenomena experienced by research subjects. The approach taken is a phenomenological approach. Data was collected by interview and questionnaire methods. The analysis used is descriptive analysis. The results showed that more than half of the female students had carried out the Clean and Healthy Behavior Program (PHBS), which was 87%, the level of knowledge about PHBS was 83.74%. Santriwati has an attitude towards PHBS of 84.5%